The role of corporate governance and managerial overconfidence in enhancing firm value: The mediating effect of sustainability reporting and moderating role of audit quality - Dewi, Putu Purnama; Wiagustini, Ni Luh Putu; Ratnadi, Ni Made Dwi; Putri, I Gusti Ayu Made Asri Dwija (Edelweiss Applied Science and Technology, 2025)
This study investigates how managerial overconfidence and corporate governance influence firm value, with sustainability reporting quality as a mediating variable and audit quality as a moderating variable. The research analyzes 393 firm-year observations from 170 non-financial companies listed on the Indonesia Stock Exchange between 2017 and 2022. Results show that both managerial overconfidence (β = 0.536, p < 0.05) and corporate governance (β = 1.222, p < 0.05) significantly enhance firm value. Sustainability reporting quality positively moderates the effect of managerial overconfidence on firm value (β = 0.233, p < 0.05), although it does not mediate the relationship between corporate governance and firm value. Additionally, audit quality strengthens the positive impact of both managerial overconfidence (β = 0.087, p < 0.05) and corporate governance (β = 0.11, p < 0.05) on firm value. The study also finds that firm size negatively affects firm value (β = -0.0766), while sales growth and firm age have no significant effect. These findings highlight the importance of strong corporate governance, confident leadership, high-quality sustainability disclosures, and credible auditing in enhancing firm value in a competitive business environment.